2009
DOI: 10.3844/ajassp.2009.1495.1501
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Comfort Assessment: A Case Study at Malaysian Automotive Industry

Abstract: Problem statement: Thermal comfort has a great influence on the productivity and satisfaction of indoor building occupants. The exposure to excessive heat during work may cause discomfort and contributed to low productivity among workers. Malaysia known with its hot and humid weather where in most of the survey study published indicated that workers in Malaysia automotive industries had exposed to excessive temperature while working. The study investigated the thermal comfort level experienced by worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The mean temperature is approximately 27°C. The relative humidity level can raise exceeding 80% (Ismail et al, 2009). In the effort of knowing the indoor thermal problems inside the LEO building, the occupants must be viewed as important contributors throughout the assessment process as they are the source complaints and a potential source of useful information that can help in assessing the extent of the problem and identifying solutions (Budaiwi, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The mean temperature is approximately 27°C. The relative humidity level can raise exceeding 80% (Ismail et al, 2009). In the effort of knowing the indoor thermal problems inside the LEO building, the occupants must be viewed as important contributors throughout the assessment process as they are the source complaints and a potential source of useful information that can help in assessing the extent of the problem and identifying solutions (Budaiwi, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Malaysia, as a country which has a hot and humid climate (Yau, Chew, & Saifullah, 2012) is essential to provide thermal comfort during office hours. Air-conditioning is one of mechanical ventilation system that widely used to provide it (Ismail et al, 2009). However, mechanical ventilation system is could be associated with IAQ problems such high levels of air contaminants due to the insufficient of airflow (Meckler, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The predictive mean vote (PMV) is a parameter for assessing thermal comfort in an occupied zone based on the conditions of metabolic rate, clothing, air speed besides temperature and relative humidity [2]. The PMV is expressed on the 7-point ASHRAE scale of thermal sensation [11].…”
Section: Predictive Mean Votementioning
confidence: 99%
“…The best one realistically hopes to achieve is a thermal environment that satisfies the majority of people in an occupied space [1]. Studies have shown that 80% of occupants is a reasonable limit for the minimum number of people who should be thermally comfortable in an environment [2]. There are passive, active and hybrid means of achieving thermal comfort.…”
Section: Introductionmentioning
confidence: 99%